Cost effective power-to-X plant using carbon dioxide from a geothermal plant to increase renewable energy penetration. (15th December 2020) - Baccioli, Andrea; Bargiacchi, Eleonora; Barsali, Stefano; Ciambellotti, Alessio; Fioriti, Davide; Giglioli, Romano; Pasini, Gianluca
Graphical abstract: Highlights: SNG and O2 are produced by a methanator coupled to an electrolyzer and a geothermal plant. Products are cost-effectively liquefied increasing their value and easing transport and storage. Selling LSNG and LOx on relevant markets makes the system cost-effective. Excess electricity available in low price hours is exploited. The system eases the integration of an increasing share of renewable generation. Abstract: In the framework of a scenario with an always increasing share of generation from variable renewable sources, the need for systems able to store energy or to convert the excess generation into useful goods is becoming of paramount importance. While several projects and pilot plants deal with direct energy storage or with the conversion of the excess generation into other energetic goods (hydrogen or methane) often overlooking economic considerations, this paper proposes a cost-effective approach in which liquified methane and oxygen are produced and sold on their specific markets, which represents one of the first profitable Power-to-X applications at current market values. The paper presents the completely new and never investigated before idea of coupling the plant with a freely available source of pure carbon dioxide from a geothermal unit, thus making it possible to produce synthetic methane to be liquefied, stored and then used in other sectors of the society. The carbon dioxide coming with the geothermal fluid is no longer released in the environment as it currently naturally happens even when not going through the geothermal facility. Detailed models of the main system components were created, and an optimization procedure was carried out. Interestingly, the revenues from the sale of liquefied oxygen are well above those coming from synthetic methane and turn the system profitable. With a proper operation planning, bidding on the electricity day-ahead-market, a large hydrogen storage system proved to be unnecessary. The results of the system optimization clearly show that this kind of systems, although conceived in a very favourable condition, can become profitable only if the energy storage function is coupled with the production of other goods services. Assuming an average electricity price of 52 €/MWh, the plant profitability is achieved for an LNG selling price of 0.45 €/kg and an LOx price around 0.30 €/kg. These figures will rapidly decrease in the near future as lower electricity prices are forecasted.